Size and sex matter: reproductive biology and determinants of offspring survival in Gazella marica. (21st June 2013) - Riesch, Rüdiger; Martin, Ryan A.; Lerp, Hannes; Plath, Martin; Wronski, Torsten
<x xml:space="preserve">Abstract</x> Environmental conditions should impact the optimal resolution of the trade‐off between offspring size and offspring number, which has a major impact on female reproductive life histories. Using breeding data collected over 13 years at the King Khalid Wildlife Research Centre (KKWRC) in Saudi Arabia, we tested the hypothesis that larger sand gazelle (Gazella marica) offspring will have lower mortality than smaller‐sized offspring; nonetheless, selection should still favour the production of larger litters (even at the cost of reduced offspring size) under favourable environmental conditions (and vice versa under poor environmental conditions). The present study provides evidence for an early fitness advantage of larger over smaller sand gazelles because offspring that were heavier at birth had higher survival rates to weaning age (90 days) and sexual maturity (365 days) than lighter offspring; also, females had higher survival rates than males. Moreover, antagonistic selection on offspring and litter size is resolved in favour of maternal fitness early in the year (i.e. high propensity for twinning), although fitness optima converge later in the year when it becomes beneficial to both offspring and mothers to produce large singletons, highlighting temporal variation in the selective regimes affecting female reproductive life histories. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 116–127.